XCL1-secreting CEA CAR-T cells enhance endogenous CD8+ T cell responses to tumor neoantigens to confer a long-term antitumor immunity - Kun Chen; Fei Zhao; Hong Zhao; Dongmei Wang; Chunfeng Qu; Zhiyuan Wu; Feifei Wang; Xing-Ning Li; Ruochan Zhang; Chentong Xiao; Yuliang Ran (Journal for ImmunoTherapy of Cancer)
Background Therapeutic efficacy of carcinoembryonic antigen (CEA)-specific chimeric antigen receptor (CAR) T cells against colorectal cancer (CRC) remains limited due to the unique characteristics and distinct microenvironments of tumor tissues. We modified CEA-specific CAR-T cells, aiming to stimulate endogenous CD8+ T cell responses against neoantigens that were derived from CEA-positive tumors destroyed by the CAR T cells.Methods In a conventional CEA CAR (reg-CAR), we modified it to express lymphotactin XCL1 and interleukin (IL)-7 genes, constructing a modified 7XCL1-CAR. By generating the CEA-specific 7XCL1-CAR T cells, we assessed their antitumor efficacy against CRC cells with varying levels of CEA expression, both in cell-cultures and in two strains of tumor-bearing syngeneic mice.Results Following retroviral transduction, 7XCL1-CAR T cells and reg-CAR T cells exhibited similar positive proportions of CEA-CAR and CD4:CD8 ratios. In co-culture system with CEA-negative CT26 cells, no differences in cytotoxicity were observed between 7XCL1-CAR and reg-CAR T cells. However, in co-culture with CT26.CEAhigh and CT26.CEAint cells, 7XCL1-CAR T cells displayed higher cytotoxicity than that reg-CAR T cells after 60 hours. On interaction with CT26.CEA-positive cells, 7XCL1-CAR T cells secreted higher levels of XCL1 and IL-7, effectively recruited the most potent cross-presenting cDC1s (type-I conventional dendritic cells), and sustained the antitumor activity of CAR-T cells. In treating mice that carried tumors derived from universally CEA-positive cells, 7XCL1-CAR T cells exhibited no difference compared with reg-CAR T cells. However, in treating mice with tumors containing both CEA-positive and CEA-negative cells, 7XCL1-CAR T cells displayed greater inhibition than that of reg-CAR-T cells. After treatment of 7XCL1-CAR T cells, tumor-bearing mice exhibited enhanced infiltration of cDC1s, maintained CAR-T activity, and generation of endogenous neoantigen-specific T cells. Consequently, 7XCL1-CAR T cell-treated mice demonstrated resistance to challenge with CEA-negative CT26 cells.Conclusion Treatment with CEA-specific, XCL1-secreting CAR-T cells for CEA-positive tumors promoted the generation of CD8+ T cells against tumor neoantigens, mediating a long-term antitumor immunity against heterogeneous CRCs.